Given
The equation is in the form
[tex]=\frac{4^{\sqrt{400}}}{4^{\sqrt{5}}}[/tex]
Simplify the above equation
To proof
As given in the question the equation is written in the form
[tex]=\frac{4^{\sqrt{400}}}{4^{\sqrt{5}}}[/tex]
By using the exponent property
when you divide powers with the same base you just have to subtract the exponents. i.e
[tex]\frac{y^{a}}{y^{b}} = y^{a-b}[/tex]
y is not equal to zero.
Now apply this property to the above equation
[tex]=4^{\sqrt{400}- \sqrt{5}}[/tex]
As
[tex]\sqrt{400} = 20[/tex]
now put this in the above equation
we get
[tex]=4^{20- \sqrt{5}}[/tex]
Hence proved